2020
DOI: 10.1111/andr.12912
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes after plaque incision and grafting for Peyronie’s disease: comparison of porcine dermal and bovine pericardium grafts

Abstract: Background Plaque incision and grafting (PEG) is one of the mainstays in surgical therapy for severe penile curvature in Peyronie’s disease (PD). Different kinds of grafts are available for covering albugineal defects during PEG, both allografts and xenografts. However, to date, none of these proved superior to others. Objectives To compare two different types of xenograft, porcine dermal matrix and bovine pericardium matrix in PEG for PD. Materials and methods From 2010 to 2019, 63 patients with PD underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 5 Interestingly, in studies by Silva-Garetton et al . 50 and Fiorillo et al , 51 75% and 80% of patients, respectively, reported penile shortening.…”
Section: Discussionmentioning
confidence: 91%
“… 5 Interestingly, in studies by Silva-Garetton et al . 50 and Fiorillo et al , 51 75% and 80% of patients, respectively, reported penile shortening.…”
Section: Discussionmentioning
confidence: 91%
“…To our centre, from 2010 to 2019, 63 patients with PD underwent corporoplasty with plaque incision/excision at single tertiary center, using two different xenografts: porcine acellular collagen matrix (25 patients-Group1) and bovine pericardium collagen matrix (38 patients-Group2). 70 For long-term evaluation of surgical outcomes multi-disciplinary questionnaires were administered, by phone interview, performed by the same physician. Overall, 53 patients completed the follow up (19 in Group 1 and 34 in Group 2).…”
Section: Personal Experiencementioning
confidence: 99%